2012
DOI: 10.4161/cc.20810
|View full text |Cite
|
Sign up to set email alerts
|

Timeless preserves telomere length by promoting efficient DNA replication through human telomeres

Abstract: A variety of telomere protection programs are utilized to preserve telomere structure. However, the complex nature of telomere maintenance remains elusive. The Timeless protein associates with the replication fork and is thought to support efficient progression of the replication fork through natural impediments, including replication fork block sites. However, the mechanism by which Timeless regulates such genomic regions is not understood. Here, we report the role of Timeless in telomere length maintenance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 69 publications
3
79
0
Order By: Relevance
“…Together with the fact the acid N-terminal domain of TRF1 is involved in fork progression, 39,52 our results suggest that the recent divergence during chordate evolution between the N-termini of TRF1 and TRF2 51 has been selected to decrease the risk of telomere damages during replication and therefore to delay replicative senescence, a process antagonized by p53-mediated TRF2 degradation.…”
Section: Discussionmentioning
confidence: 61%
“…Together with the fact the acid N-terminal domain of TRF1 is involved in fork progression, 39,52 our results suggest that the recent divergence during chordate evolution between the N-termini of TRF1 and TRF2 51 has been selected to decrease the risk of telomere damages during replication and therefore to delay replicative senescence, a process antagonized by p53-mediated TRF2 degradation.…”
Section: Discussionmentioning
confidence: 61%
“…Recent studies have shown that TIMELESS contributes to the replication of difficultto-replicate DNA, including centromeric DNA, trinucleotide repeats and telomeres. 33,35,36 Considering that TIM-TIPIN interacts with CMG helicase components, AND1 and polymerases ε, δ and α, and that TIM-TIPIN-deficient cells showed spontaneous activation of CHK1, TIM-TIPIN may provide a link between DNA unwinding and polymerization to preserve stalled or uncoupled replication forks in a state competent for restart. 45 The mechanism(s) by which TIM-TIPIN orthologs might protect/restart replication forks independently of CHK1 activation remains to be fully characterized.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35][36] TIMELESS, TIPIN and CLASPIN orthologs travel with the replication fork 26,37,38 and interact with replisome components (including MCM helicase subunits, replicative polymerases, AND1, PCNA and RPA). 15,39,40 Although TIM-TIPIN mediates ATR-CHK1 signaling in response to experimentally induced replication stress, loss of TIM-TIPIN is associated with increased ssDNA and activation of CHK1, 41 suggesting that TIMELESS and TIPIN have functions for preservation of replication fork structure that are independent of ATR-CHK1 signaling.…”
Section: Introductionmentioning
confidence: 99%
“…RTEL1 contains a proliferating cell nuclear antigen (PCNA)-interacting motif (Ding et al 2004) that is required for the repression of the fragile telomere phenotype (Vannier et al 2013). How TRF1 interacts with PCNA-bound RTEL1 to manage telomere replication merits further investigation, as do the roles of Timeless and Topoisomerase IIa (Leman et al 2012;d'Alcontres et al 2014). …”
Section: The Role Of Blm At Telomeresmentioning
confidence: 99%
“…Upon inhibition of the BLM or RTEL1 but not the WRN helicase, mouse cells show a fragile telomere phenotype, and as knockdown of either BLM or RTEL1 does not further exacerbate the phenotype of TRF1 deletion, they appear to act in the TRF1 pathway (Sfeir et al 2009). In addition to BLM and RTEL1, Topoisomerase IIa and Timeless have been implicated in the mechanism by which TRF1 guards against the fragile telomere phenotype (Leman et al 2012;d'Alcontres et al 2014). …”
mentioning
confidence: 99%